A Review of Monitoring Techniques for Livestock Respiration and Sounds - Handa, Divya; Peschel, Joshua M. (Frontiers in Animal Science, 2022)
This article reviews the technologies used to monitor the respiration rates of livestock. Livestock respiration is commonly assessed visually by observing abdomen fluctuation or by counting the flank movement of the nostrils; however, these traditional methods are time consuming, subjective, being therefore impractical for large-scale operations and must rely on automation. Contact and non-contact technologies are used to automatically monitor respiration rate; contact technologies (e.g., accelerometers, pressure sensors, and thermistors) utilize sensors that are physically mounted on livestock while non-contact technologies (e.g., computer vision, thermography, and sound analysis) enable a non-invasive method of monitoring respiration. This work summarizes the advantages and disadvantages of contact and non-contact technologies and discusses the emerging role of non-contact sensors in automating monitoring for large-scale farming operations. This work is the first in-depth examination of automated monitoring technologies for livestock respiratory diseases; the findings and recommendations are important for livestock researchers and practitioners who can gain a better understanding of these different technologies, especially emerging non-contact sensing.